The importance of rugby game-related statistics to discriminate winners and losers at the elite level competitions in close and balanced games - Vaz, Luis; Mouchet, Alain; Carreras, David; Morente-Oria, Honorato Fernando (Taylor & Francis, 2011)
The aim of the current study was to identify the Rugby game-related statistics that discriminated between winning and losing teams in International Rugby Board (IRB) competitions (World Cup and Six Nations) and Super Twelve Tournament (S12) in close and balanced games. A cluster analysis was conducted to establish, according to game balanced games group was selected for further analysis. An analysis of the structure coefficients (SC) obtained through a discriminant analysis allowed the identification of the most powerful game-related statistics in discriminating between winning and losing teams. The results showed that when compared, IRB and S12 close and balanced games were evident, although significant between-games differences were found for all of the analysed group clusters. This suggests that for close and balanced games a general profile may be created, which is probably specific to each team, and may indicate the strengths and weaknesses of that specific competition groups.
Trabajo realizado por profesionales del RUGBY para determinar la influencia de ciertos aspectos del juego en ganar o perder partidos. https://openpolicyfinder.jisc.ac.uk/id/publication/33259
Keywords: Deportes - Estadísticas; Rugby; Statistics; Winners and losers